What is the Correct Name for Ipomoea muricata Jacq.? - Oza, G M (Annals of Arid Zone, 2016)
The correct name of the Purple Moonflower, originating from Suratte (Surat) in Western India. is presented as Ipomoea turbinata Lag. in this note, The taxon exhibits little variation and since it has a world-wide range, it carries many synonyms.